FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP AUDIT REPORT LAG (STUDI EMPIRIS PADA EMITEN INDUSTRI KEUANGAN DI BEI) - Ja’far Aziz Hariza; Nining Ika Wahyuni; Siti Maria Wardayati (Universitas Jember, 2012)
The timeliness of annual reports depend on the timeliness of auditor’s performance. The more timeline of publishing annual reports, more benefit can be delivered. This research investigates the factors influencing audit report lag in Indonesia. Sample of the research comprises 42 companies listed in Indonesian Stock Exchange during the year of 2010. The audit report lag for each sample companies ranged from a minimum interval of 25 days to a maximum interval of 129 days and 72 days in the average. Five hypotheses relating audit report lag to company size, profitability, leverage, auditor size, and audit opinion are tested in the research. The results of multiple linear regression support the alternate hypotheses put before except for the company size and leverage. Keywords: audit report lag, company size, profitability, leverage, auditor size, audit opinion.